Bank relationship and contractual flexibility: Evidence from covenant enforcement - Gam, Yong Kyu; Liu, Chunbo (Contemporary Accounting Research, 2024)
This paper investigates how banks utilize soft information to provide contractual flexibility in loan covenant enforcement. We find that relationship lenders are significantly less likely than non‐relationship lenders to enforce covenants for material violations when borrowers are potentially in breach of financial covenants. The mitigation of information asymmetry by relationship lending, as opposed to alternative explanations, serves as the underlying mechanism. Furthermore, relationship borrowers with potential covenant breaches are less likely to experience increases in loan interest rates after renegotiation, to adopt conservative financial or investment policies, or to file for bankruptcy. Following potential covenant breaches of borrowers, relationship banks are better able to preserve regulatory capital and secure future lending business. Our findings suggest that soft information accumulated during lending relationships is vital for banks to provide contractual flexibility.